Non Invasive Cardiac Output Evaluation with CO2 Rebreathing Method for CRT Patients (International Journal of Statistics in Medical Research, 2016)
Background: Cardiac resynchronization therapy with ICD (CRT-D) or pacemaker (CRT-P) is useful to reverse the deleterious effects of ventricular dyssynchronia in heart failure (HF) patients. To determinate the responders patients, hemodynamic parameters are difficult to evaluate during follow-up, due to the invasivity of the procedures. We compare hemodynamic response to CRT with cardiac output, not invasively detected (CO2 rebreathing method, Innocor system), with conventional clinical, functional and echocardiographic parameters.Methods: We enrolled 29 patients affected by end-stage dilated cardiomyopathy treated with CRT-P/CRT-D according to the latest guidelines (NYHA class II-IV, left ventricular ejection fraction [LVEF] ≤ 35%, QRS ≥ 120 ms, sinus rhythm, optimal medical therapy). Patients were evaluated before and after CRT (3 months), considering: NYHA class, Quality of Life score (Minnesota Living with Heart Failure questionnaire), QRS width, echocardiographic parameters (diastolic and systolic left ventricular volumes and related LVEF), six minutes walking test (6MWT) and cardiac output (detected with Innocor system).Results: Our data showed a significant improvement in Innocor cardiac output 3 months after CRT implant compared to baseline (4.01±0.72 vs 4.48±0.59 l/min, p=0.001). The percentage improvement in cardiac output correlates with the percentage increase in LVEF (25±6% vs 30±7%; r=0.541). The correlation is not statistically significant with NYHA class (from 2.52±0.73 to 1.78±0.60; r=0.098), QoL (from 22.57±15.37 to 9.91±9.14 score; r=0.231) and exercise tolerance (from 390±50 to 437±54 meters; r=0.144).Conclusions: The Innocor system is a promising non-invasive method to assess the cardiac output at baseline and during follow up in HF patients treated with CRT.